Morphological diversity of Neuquensaurus Powell, 1992 (Sauropoda; Titanosauria): insights from geometric morphometrics applied to the vertebral centrum shape - Zurriaguz, Virginia Laura (2016)
Neuquensaurus is a small-sized titanosaur from the Upper Cretaceous of Patagonia, Argentina, for which two species were recognised in the past (Neuquensaurus australis and Neuquensaurus robustus). Given that such division was only based on the relative robustness of the limb bones, the validity of the species N. robustus has been questioned. In this work, we studied the morphological variation of the vertebrae of this genus through geometric morphometric techniques and the description of relevant anatomical features in order to assess if there are one or more morphotypes within Neuquensaurus. We found two distinguishable morphotypes, one belonging to N. australis and other that includes specimens assigned to both N. australis and N. robustus. The occurrence of a posterior cervical vertebra with a particular anatomical feature (i.e. four sprl) could indicate the presence of another taxon than N. australis in the studied sample. Although the validity of the species N. robustus cannot be discussed on the basis of the current data, our study supports the hypothesis of at least two different morphotypes of Neuquensaurus (which could be related to different taxa).